Pengaruh Religiusitas dan Gender terhadap Kepatuhan Wajib Pajak Orang Pribadi - Frista Frista; Umi Murtini; Kenny Fernando; Fellinne Pirenne Kusdiono (Akuntabilitas, 2021)
One of the problems faced by Indonesia is the low level of the tax ratio. In order to increase state revenue from the tax sector, efforts should be made to increase voluntary tax compliance. This study aims to examine the effect of religiosity and gender on tax compliance. The method used is quantitative “mix methods” using regression analysis and descriptive analysis of the questionnaire obtained through “convenience sampling methods”. The results showed that religiosity and gender had a positive effect on tax compliance. The higher the level of religiosity, the level of taxpayer compliance will also increase. This research contributes to providing input to tax authorities to increase tax awareness through outreach in religious communities by involving women.